2011
DOI: 10.2298/mpns1110471m
|View full text |Cite
|
Sign up to set email alerts
|

Thromboprophylaxis implementation during pregnancy in women with recurrent foetal losses and thrombophilia

Abstract: Recurrent foetal loss is a significant clinical problem, occurring in 1-5% of reproductive females. Inherited or acquired thrombophilia has been diagnosed in 50-65% of women with history of unexplained foetal loss. The low molecular weight heparin was applied in 24 women with inherited thrombophilia and previous recurrent foetal loss and in 6 women with primary antiphospholipid syndrome throughout their following pregnancies. The dose of low molecular weight heparin for the majority of women was 35-75 u/kg. Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
1
16
0
2
Order By: Relevance
“…However, if we are able to determine more risk factors and causative markers for RPL which can be strategically applied based on their association with unexplained RPL. Appropriate treatment could be given to these patients in subsequent pregnancies as beneficial effect of anticoagulation has been shown in some reports [13,14]. Inherited thrombophilia and APLAs are important risk factors for PL.…”
Section: Discussionmentioning
confidence: 99%
“…However, if we are able to determine more risk factors and causative markers for RPL which can be strategically applied based on their association with unexplained RPL. Appropriate treatment could be given to these patients in subsequent pregnancies as beneficial effect of anticoagulation has been shown in some reports [13,14]. Inherited thrombophilia and APLAs are important risk factors for PL.…”
Section: Discussionmentioning
confidence: 99%
“…A taxa de sucesso gestacional em gestantes com marcadores trombofilicos, apresentada em estudo recente foi de 76% (29/38), indicando que a HBPM pode ser opção terapêutica promissora em gestantes com perdas fetais e trombofilias 27 .…”
Section: Discussionunclassified
“…Vários estudos são focados no uso profilático de agentes antitrombóticos, isoladamente ou em combinação com prednisona, aspirina, ácido fólico e progesterona 14,24,27,28 em gestantes com ou sem trombofilias. No presente estudo, a utilização da terapia anticoagulante foi indicada em gestantes com histórico obstétrico anterior adverso e portadoras de marcadores sorológicos para trombofilias hereditárias/adquiridas.…”
Section: Discussionunclassified
“…These results suggest that LMWH prophylaxis reduces the risk of obstetric complications in carriers of FVL and/or PTG, particularly in those with previous obstetric events. Mitic et al also reported significant improvement of pregnancy outcome after implementation of thromboprophylaxis in Serbian patients with inherited thrombophilia and previous pregnancy losses [39].…”
Section: Genetics and Treatment Of Reproductive Adversity In Thrombopmentioning
confidence: 92%